Modelling one-dimensional elastic diffusion processes in an orthotropic solid cylinder under unsteady volumetric perturbations - Andrei V Zemskov; Nikolay A. Zverev; Dmitrii V. Tarlakovskii (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2022)
A polar-symmetric elastic diffusion problem is considered for an orthotropic multicomponent homogeneous cylinder under uniformly distributed radial unsteady volumetric perturbations. Coupled elastic diffusion equations in a cylindrical coordinate system is used as a mathematical model. The model takes into account a relaxation of diffusion effects implying finite propagation speed of diffusion perturbations.